Pre- and post-partum seric biochemical variables of Lacaune ewes naturally infected by gastrointestinal parasites. (July 2016) - Balzan, Alexandre; Machado, Gustavo; Bottari, Nathieli; Volpato, Andreia; Grosskopf, Rhayana; Boito, Jhonatan; Cazarotto, Chrystian; Schetinger, Maria; Morsch, Vera; Silva, Aleksandro
Abstract The main objective of the present study was to evaluate the biochemical profile of the Lacaune ewes naturally infected by gastrointestinal parasites in the pre- and post-partum period. Ewes with similar age and weight, primiparas in the final stage of gestation, totaling 24 animals were selected. Sampling days were 10 and 2 for pre-partum and 2, 6, and 12 days for post-partum to evaluate total proteins, albumin, globulin, cholesterol, triglycerides, and urea levels, in addition to thiobarbituric acid reactive substances (TBARS), reactive oxygen species (ROS), and glutathione S-transferase (GST). Fecal examination by McMaster method was performed during bleeding, and based on the number of eggs per gram of feces (EPG), the animals were divided into two groups: A (sheep with EPG <1000) and B (sheep with EPG >1000) to evaluate the effect of the parasitic load. Statistical analyses of biochemical parameters and EPG were performed taking into account groups, evaluated each time of sampling and over time, as well as without considering the groups, comparing pre- and post-partum and over time. It was possible to verify that the influence of time had a significant (P  < 0.01) impact on cholesterol, triglycerides, total proteins, albumin, globulin, TBARS, and GST specifically among sampling time. When time of collection was considered, there were some differences between groups A and B for the variables: triglycerides (day 6 post-partum) and globulin (day 2 pre-partum). It is concluded that the parasitic load did influence seric levels of the urea, triglycerides, and globulins on a determined time.